Pengaruh Rekrutmen dan Penempatan Kerja Terhadap Kinerja Karyawan PT. Artdeco Inti Kreasi - Muhammad Fadly Prambudi; Syahrum Agung; Diah Yudhawati (Institute of Advanced Knowledge and Science, 2023)
This study aims to determine the effect of recruitment and job placement on the performance of PT Artdeco Inti Kreasi employees. This type of research is quantitative. The population of this study were employees of PT Artdeco Inti Kreasi. The analysis used is quantitative technique using saturated sampling technique with a population of 40 respondents. This research instrument is a questionnaire. The results of the research instrument test used multiple regression analysis tests, t tests, f tests. The results of the analysis show that recruitment and job placement have a significant effect on employee performance with the results of multiple regression analysis tests. The results of the recruitment t test obtained the results of the t test < t table (0.936 < 2.026) means Ho1 is accepted Ha1 is rejected, the job placement t test obtained the results (12.800> 2.026) means Ho2 is rejected and Ha2 is accepted, and the f test results are (351.657> 3.252) meaning Ho3 is rejected Ha3 is accepted. Based on the results of this data, it can be concluded that recruitment and job placement affect the performance of employees of PT Artdeco Inti Kreasi.